Lone parenthood in the COVID‐19 context: Israeli single gay fathers' perspective. Issue 4 (5th April 2022) - Tsfati, Maya; Segal‐Engelchin, Dorit
Abstract: This article focuses on Israeli single gay fathers, using the Stress Process Model (SPM) as a framework to investigate their fathering experiences during the COVID‐19 pandemic. Thematic analysis of 15 in‐depth semi‐structured interviews with Israeli single gay fathers during the third national lockdown revealed that their parenting experiences during the pandemic were shaped by both COVID‐related stress exposure and interpersonal resources, which the fathers viewed as interactive. These fathers described three main pandemic‐specific stressors: financial insecurity and workplace transformation, feelings of loneliness and isolation and health‐related fears. Our findings highlight the cumulative effects of these stressors on the fathers' well‐being. The fathers also described the ways in which their interpersonal resources (i.e., social networks and strengthened relationship with their children during the pandemic) facilitated their coping with the pandemic‐related stressors. The study highlights the need for social workers to recognize the emerging family forms and to broaden their approach to parents during a time of ongoing community crisis, by addressing the differential effects on parents in diverse family structures.